The Role of the Diaphragm in Postural Stability and Visceral Function in Parkinson’s Disease - Yu, Xin; Jiang, Hong-ying; Zhang, Chen-xi; Jin, Zhao-hui; Gao, Lei; Wang, Rui-dan; Fang, Jin-ping; Su, Yuan; Xi, Jia-ning; Fang, Bo-yan (Frontiers in Aging Neuroscience, 2021)
Background: In normal subjects, the diaphragm plays a key functional role in postural stability, articulation, respiration, defecation, and urination. Objectives: The aim of this study was to investigate the role of the diaphragm in postural stability and visceral function in patients with Parkinson’s disease (PD) and to compare the diaphragm function by gender, Hoehn and Yahr (H&Y) staging, and motor subtypes. Methods: In total, 79 patients were enrolled in this cross-sectional study. The severity of the disease was assessed by the Movement Disorder Society-Unified Parkinson’s Disease Rating Scale III and by H&Y staging. Postural stability was quantitatively recorded, and respiratory function was evaluated by spirometry. Several scales were used to evaluate visceral function in patients with PD. In addition, diaphragm ultrasound was used to measure the excursion, contraction velocity, and thickness of the diaphragm during quiet breathing, deep breathing, and the sniff test. Significant features were selected by the least absolute shrinkage and selection operator (LASSO) regression and fitted in the multivariate linear regression and Pearson’s correlation analysis. Results: Diaphragm thickness and excursion during quiet breathing were significantly different between men and women and between H&Y stage 1–2 and stage 2.5–3, whereas the diaphragm function was not influenced by motor subtypes. It was shown that the diaphragmatic function was significantly correlated with postural stability, voice function, respiratory function, constipation, and urological function to varying degrees in patients with PD. Conclusion: The diaphragmatic function is associated with dysfunction in PD although it remains unclear as to whether the observed changes in the diaphragm are primary or secondary.